Academic patenting: the importance of industry support - Lawson, Cornelia (Springer, 2013)
This paper provides evidence that university-industry collaboration is important for turning commercial opportunities into patents. The results suggest that researchers who receive a large share of research grants from industry have a higher propensity to file a patent. Small dissemination grants generally exert a positive effect, whether they come from industry or not. It also finds that these interactions do not increase the number of industry owned patents alone but benefit universities’ commercialisation efforts in general.